Leadership in Action : Face to Face - Valuing Evaluation - A Conversation with Laura C. Leviton - Rush, Editor Stephen (Center for Creative Leadership, 2005)
Leviton holds a Ph. D. degree in social psychology from the University of Kansas and has completed postdoctoral training in evaluation research at Northwestern University. She recently spoke with Kelly Hannum, an enterprise associate and project manager with CCL's Global Leadership and Diversity research group.